FUNCTIONAL CLASSES AND CLINICAL CHARACTERISTICS OF CHRONIC HEART FAILURE IN PATIENTS WITH ATRIAL FIBRILLATION AND/OR FLUTTER AFTER RADIOFREQUENCY ABLATION - Zolotarova, T. V.; Brynza, M. S.; Yabluchanskiy, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The combination of atrial fibrillation and/or flutter and chronic heart failure is a frequent problem for many patients. Radiofrequency ablation is effective in the strategy for controlling the rhythm of patients with atrial fibrillation and/or flutter, but always requires concomitant therapeutic support. The study involved 70 patients with atrial fibrillation and/or flutter after radiofrequency ablation which were divided into groups according to the functional class of chronic heart failure. Gender and age of patients; types of ischemic heart disease; stages of chronic heart failure; degrees of arterial hypertension; the form of atrial fibrillation and flutter; class EHRA; the presence of diabetes mellitus type 1 or 2 we evaluated. The female sex prevailed in the group of II functional class of chronic heart failure than in I functional class or III functional class. Ischemic heart disease, first of all angina of effort, in patients with III functional class of chronic heart failure was significantly more frequent. In group of III functional class of chronic heart failure there were significantly more patients with 3 degrees of arterial hypertension. Male patients, regardless of functional class of chronic heart failure, more often than females are conducted invasive methods of treatment for atrial fibrillation/flutter. With increasing of functional class of angina the functional class of chronic heart failure is increasing. Among patients II and III functional class of chronic heart failure prevails the arterial hypertension III degree, which may be a predictor of adverse prognosis.